(untitled) (Nueva Epoca, 2020)
The work proposes to delimit the legal framework and scope of concept of business because the Unified Code introduces it, without defining it, through the obligation to keep accounting. The study of the differences between subjects who carry out «organized economic activity» will be approached; «business owners» and «business establishment owners». The contribution of various doctrinal positions and the most relevant comparative law regulations on the subject will be examined.